The office survival guide Surefire Techiques for dealing with challeging people and situations - Puder - York Marilyn (MC Graw Hill, 2006)
A boss who issues impossible or unethical demands, a shark of a co-worker who'll use any means to get ahead, a troubled or troublesome assistant--these are among the thorny issues faced by employees at every level of organizational life. Not only do they make the office an unpleasant and stressful environment; if they're managed poorly, tough situations and difficult dilemmas can be real career killers. In THE OFFICE SURVIVAL GUIDE, clinical psychologist and executive coach Marilyn Puder-York describes the top ten trickiest workplace problems, and presents her unique two-part approach to solving them.